Comparison of Learning Achievement in Teaching Thai Language Subject on Spelling Section Between Using Practice Book and Normal Teaching for Students in Prathomsuksa 2, Wat Ladprao School - bunmakham, nisarat; Jetsadawiroj, Siripat (Journal of Modern Learning Development, 2023)
This research aims (1) to create and investigate efficiency of Thai language spelling skill development exercises of primary 2 students which needs to be effective at criteria 80/80, (2) to compare the achievement of Thai language learning which is Thai spelling rules of primary 2 students between teaching by using spelling skill development exercises of Thai language and teaching by traditional teaching style. (3) to study students’ satisfaction of learning Thai spelling rules by using Thai language spelling skill development exercises. The participants of this study consisted of Primary 2 students studying at Wat Latphrao School in second semester of academic year 2021 by using simple random sampling.The students were separated into two classes which were primary 2/1 and primary 2/2 students by drawing lots. Primary 2/1 students which were sample group learned Thai spelling rules by using spelling skill development exercises of Thai language, whereas primary 2/2 students which were control group learned Thai spelling rules in traditional teaching method. The instruments used in this research were composed of (1) spelling skill development exercises of Thai language (2) Thai language lesson plan by using spelling skill development exercises of Thai language (3) Thai language lesson plan by traditional teaching method (4) 30 items of 4 multiple choices of Thai language learning achievement test (5) satisfaction survey of primary 2 students by using spelling skill development exercises of Thai language.In addition, the statistics applied in this research were mean (x), standard deviation (S.D.), E1/E2 and t-test independent. The results showed that (1) applying spelling skill development exercises of Thai language could enhance the efficiency of learning Thai spelling rules, and the value of the efficiency was 81.92/81.33 which met the set criteria. (2) the learning achievement by using spelling skill development exercises of Thai language was statistically significant higher than learning by traditional teaching method at the .05 level. (3) the students’ satisfaction of learning Thai spelling rules by using spelling skill development exercises of Thai language was found at the highest level that was x = 4.50 and S.D. = 0.03.